2019
DOI: 10.1002/jcp.28514
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: CCR5 silencing reduces inflammatory response, inhibits viability, and promotes apoptosis of synovial cells in rat models of rheumatoid arthritis through the MAPK signaling pathway

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disorder that can, in severe cases, lead to disability. CC chemokine receptor (CCR), an integral membrane protein, has been suggested to play a key role in the RA developmentThis study is to explore the role of CCR5 silencing in inflammatory response, viability, and apoptosis of synovial cells in RA rats by inactivating the mitogen‐activated protein kinase (MAPK) signaling pathway. Microarray analysis was conducted to screen out differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Studies have shown that in drug-induced liver injury, CCR5 activates M1 polarization and prevents M2 polarization via the MAPK pathway (51,52). Another study demonstrated that CCR5 silencing inhibits the inflammatory response in rheumatoid arthritis rats by inhibiting the MAPK pathway, and also inhibits viability and promotes synoviocyte apoptosis (53). Ang II has been shown to promote cardiac tissue growth and contribute to pressure overload-induced cardiac hypertrophy (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in drug-induced liver injury, CCR5 activates M1 polarization and prevents M2 polarization via the MAPK pathway (51,52). Another study demonstrated that CCR5 silencing inhibits the inflammatory response in rheumatoid arthritis rats by inhibiting the MAPK pathway, and also inhibits viability and promotes synoviocyte apoptosis (53). Ang II has been shown to promote cardiac tissue growth and contribute to pressure overload-induced cardiac hypertrophy (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of such IFN-γ secreting CCR5 + CD4+ T cells into the RA joint cavity is regulated by the synovial microenvironment [28]. On the other hand, CCR5 silencing suppresses inflammatory response in RA by inhibiting synovial cell viability but promoting apoptosis [29]. Another source of CCR5 in RA are Vδ2 T cells which infiltrated into the synovium under the influence of high levels of TNF-α [30].…”
Section: Discussionmentioning
confidence: 99%
“…The in ltration of such IFN-γ secreting CCR5+CD4+ T cells into the RA joint cavity is regulated by the synovial microenvironment [29]. On the other hand, CCR5 silencing suppresses in ammatory response in RA by inhibiting synovial cell viability but promoting apoptosis [30]. Another source of CCR5 in RA are Vδ2 T cells which in ltrated into the synovium under the in uence of high levels of TNF-α [31].…”
Section: Discussionmentioning
confidence: 99%